The Challenges of the Polylogue. Towards Miglena Nikolchina, Meaning and Matricide: Предизвиците на полилогот. Кон Миглена Николчина, Смисла и мајкоубиство - Stefoska, Irena; Tasev, Saše (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Irena Stefoska | Ирена Стефоска Title (English): The Challenges of the Polylogue. Towards Miglena Nikolchina, Meaning and Matricide Title (Macedonian): Предизвиците на полилогот. Кон Миглена Николчина, Смисла и мајкоубиство Translated by (Macedonian to English): Saše Tasev | Саше Тасев Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 236-237 Page Count: 2 Citation (English): Irena Stefoska, “The Challenges of the Polylogue. Towards Miglena Nikolchina, Meaning and Matricide,” translated from the Macedonian by Saše Tasev, Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 236-237. Citation (Macedonian): Ирена Стефоска, „Предизвиците на полилогот. Кон Миглена Николчина, Смисла и мајкоубиство“, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 236-237.